GAMBARAN TINGKAT PENGETAHUAN PERSONAL HYGIENE TENTANG MENSTRUASI PADA SISWI SMP - Zaim Anshari (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
During menstruation blood vessels in the uterus are very easily infected because germs easily enter and cause diseases of the reproductive tract. Some of the most common disorders are vaginal discharge and pruritus vulvae (vaginal itching). However, this complaint can be prevented by maintaining the cleanliness of the female organs early on, namely with good menstrual personal hygiene. This study aims to describe the level of personal hygiene knowledge about menstruation. This research is a descriptive study with a cross-sectional approach, with a total sample of 90 people taken by total sampling technique. The results showed that the majority of respondents had enough personal hygiene behavior as many as 82 people (91.1%), while good menstrual personal hygiene behavior was 3 people (3.3%), and respondents who had behaviors classified as less than 5 people ( 5.6%). Based on complaints on reproductive organs, respondents who experienced vaginal discharge were 85 people (94.4%) and itching around the genitals was around 83 people (92.2%).